Purposeful search and characteristic of anti-inflammatory activity of sodium (3-R-2-оxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)alkylcarboxylates and their halogen containing analogues - V. V. Yakubovska; N. М. Seredinska; О. Yu. Voskoboynik; G. І. Stepanyuk; S. І. Kovalenko (Zaporozhye State Medical University, 2016)
Aim. The approaches for creating novel agents with anti-inflammatory activity among sodium (3-R-2-oxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)alkylcarboxylates and their halogen containing analogues were described in presented article. Methods and results. Mentioned methods have been based on combination of «in silico» screening with experimental studies. Affinity of studied compounds to the active center of COX-1 and COX-2 enzymes has been shown. Conducted visualization of compound - active site complex allowed to suppose the presence of anti-inflammatory activity of studied compounds. Conclusions. It was established, that sodium (3-R-2-oxo-2Н-[1,2,4]triazino[2,3-c]quinazoline-6-yl)alkylcarboxylates and their halogen-containing analogues reveal anti-inflammatory activity, the most active was compound DSK-38 (ED50 - 4 mg/kg as against 8 mg/kg of diclofenac sodium). «Structure-activity» relationships features among studied compounds have been discussed.